Interoperabilidad de una aplicación multiplataforma para la Geolocalización de Farmacias del Cantón Riobamba, utilizando servicios web tipo rest - Basantes Granizo, Fernando Patricio (2019)
The purpose of this research is to analyze the interoperability of a multiplatform application for the geolocation of pharmacies in the Riobamba canton, using REST-type web services. For the design and implementation of the multiplatform mobile application, the Ionic framework and the Mobile D methodology were used, which aims to deliver a fully functional application in a short time based on its five phases: exploration, initialization, production, stabilization and System tests For the interoperability assessment between the multiplatform application and the web services of the REST type, interoperability quality metrics based on the ISO / IEC 9126-2 and ISO / IEC 25010 standards were analyzed, determining the latter as the ideal for measuring interoperability, using the model called service level based on variables such as: response time and defined time, depending on the number of requests made to the cross-platform application. For simulation of simultaneous requests in real time, JMeter configured for mobile applications was used. According to the results of the research, it can be said that REST-type web services are interoperable with cross-platform applications for geolocation of pharmacies with a value greater than 91% on Android and IOS platforms, the latter having the best level percentage of service, the device technology being a key factor.